Hakikat Pendidikan Islam - Alihan Satra; Muhammad Rizki Ramadhani; Oka Putra Pradana Wahyuda (Advances In Education Journal, 2025)
Educators hold a central role in Islamic education as murabbi (spiritual guides), mu'allim (knowledge transmitters), and muaddib (character builders), directing students' innate nature toward moral perfection and closeness to Allah. This essence draws from the Quran, such as QS. Al-Isra':24 and Ar-Rahman:2, along with Hadith, demanding competencies in personality, pedagogy, professionalism, social skills, and spirituality. Ideal Educator Traits Key virtues include patience, honesty, gentleness, compassion, and anger control as primary role models. Qualifications encompass noble morals, broad knowledge, and a divinely oriented (rubbaniyah) approach.Views of Islamic Education Figures Hamka views teachers as shapers of faithful generations through morals and teaching methods. Al-Ghazali prioritizes drawing near to Allah and character cultivation, while Basiuni Imran stresses sincerity and integration of religious and general knowledge. Their duties involve motivating, facilitating learning, and providing daily examples to optimize students' cognitive, affective, and psychomotor potentials.